Cultural Significance Analysis to Support the Valuation of Non Timber Forest Products of the Malay Community in Tanjung Jabung, Jambi, Sumatera - Esti Munawaroh; Yupi Isnaini; Purity Sabila Ajiningrum; Siti Susiarti; Y Purwanto (The Ethnobiological Society of Indonesia, 2020)
The study of utilizing the diversity of non-timber forest product species by testing the value of cultural importance or Index of Cultural Significance (ICS) analysis aims to identify the species of non-timber forest products with highest importance value for local communities. The results of this study documented (1) list of species of non-timber forest products that have an important role in the Malay community in Tanjung Jabung, Jambi, including foodstuffs (51-77 plants), vegetable ingredients (21 plants), medicinal materials (> 77 plants), equipment materials (62 plants), pulp and paper materials (27 plants), and other non-timber forest products; (2) list of species of the potential non-timber forest products to be further developed as fruit-producing plants (12 species), vegetables (10 species), medicinal plants (6 species), pulp and paper-based plants (6 species), plywood (18 species), basic materials for manufacturing equipment, arts and other local technology (8 species); and (3) basic data on economic valuation studies of non-timber forest products. The potential species that have high importance value to be cultivated plants were rambai (Baccaurea spp.), cempunik (Artocarpus hispidum), durian (Durio zibethinus, Durio oxleyanus, and Durio spp.), and rambutan (Nephelium lappaceum and Nephelium spp.) for fruits, rotan jernang (Calamus draco and Calamus spp.) as a medicinal material, and other uses. Specifically the diversity of potential species of non-timber forest products will be discussed in this paper.